2017
DOI: 10.1111/appy.12286
|View full text |Cite
|
Sign up to set email alerts
|

Association of recent gay‐related stressful events and emotional distress with suicidal behaviors over 12 months in Chinese men who have sex with men

Abstract: More efforts to reduce GRSE are worth investigating as a strategy to reduce suicidal thoughts and behaviors in Chinese MSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…Thus the result could be partially attributed to the cross-study variations in methodology (e.g., sample characteristics, definition and measurement of IPV). We also found a prevalence of 36.0% of depression in the MSM sample, which is comparable to the prevalence reported in previous studies among MSM in China [40,41]. Younger age and lower income level were associated with increased risk of depression, corroborating with prior studies among Chinese MSM [42,43].…”
Section: Discussionsupporting
confidence: 90%
“…Thus the result could be partially attributed to the cross-study variations in methodology (e.g., sample characteristics, definition and measurement of IPV). We also found a prevalence of 36.0% of depression in the MSM sample, which is comparable to the prevalence reported in previous studies among MSM in China [40,41]. Younger age and lower income level were associated with increased risk of depression, corroborating with prior studies among Chinese MSM [42,43].…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, depression was most strongly linked to workplace-based gay-related stressful events (e.g., "trouble with boss or supervisor about same-sex behavior") [53]. In addition, "Getting in trouble with the police because of same-sex behavior" as a stressful event was associated with highest elevated risks of suicidal ideation, plan, and attempt, though the overall prevalence of this event was low [73].…”
Section: Distal Sexual Minority Stress and Mental Healthmentioning
confidence: 99%
“…A longitudinal study in Beijing and a cross-sectional survey of a national sample of MSM in China reported no associations between experiences of discrimination (or enacted sexual identity stigma) and psychological distress, although both studies found discrimination to be associated with sexual risk behaviors [31,102]. However, a study with MSM in Liaoning Province revealed that gay-related stressful life events in the past 3 months were associated with elevated risks of depression and suicidal behaviors [53,73]. Specifically, depression was most strongly linked to workplace-based gay-related stressful events (e.g., "trouble with boss or supervisor about same-sex behavior") [53].…”
Section: Distal Sexual Minority Stress and Mental Healthmentioning
confidence: 99%
“…Anxiety was mainly measured with the Self-rating Anxiety Scale (SAS) (Zung, 1971) and the Generalised Anxiety Disorder Scale-7 (GAD-7) (Spitzer et al, 2006), used in 17 and 4 studies, respectively. The measurement Epidemiology and Psychiatric Sciences of suicide (suicide ideation, suicide plans or suicide attempts) based on a single item, except for two studies (Yu and Xiao, 2017;Yu et al, 2018), used standardised scales [a section of the World Mental Health Composite International Diagnostic Interview (WMH-CIDI)] (Kessler and Ustün, 2004) and a shortened 6-item version of the suicide questionnaire designed by Kessler et al (2005). The recall time to measure suicide included 'over the past week', 'over the past six months', 'over the past year', 'since HIV diagnosis' and 'lifetime'.…”
Section: Study Characteristicsmentioning
confidence: 99%